Green route to fabrication of Semal-ZnO nanoparticles for efficient solar-driven catalysis of noxious dyes in diverse aquatic environments - Lal, Ratan; Gour, Tripti; Dave, Narendra; Singh, Niharika; Yadav, Jigyasu; Khan, Afshin; Jain, Akshita; Agarwal, Lokesh Kumar; Sharma, Yogesh Kumar; Sharma, Kuldeep (Frontiers in Chemistry, 2024)
This study successfully demonstrated a sustainable and environmentally friendly approach for the synthesis of Kapok-ZnO nanoparticles (NPs) using the aqueous leaf extract of Bombax ceiba L. The obtained NPs exhibited an absorption peak at approximately 390 nm in the UV-visible spectrum and an energy gap (Eg) value of 3.11 eV. The detailed analysis of the morphology and particle size using various spectroscopic and microscopic techniques, XRD, FE-SEM with EDS, and HR-TEM revealed crystallographic peaks assigned to the hexagonal phase with an average crystal size of 17 nm. The obtained Kapok-ZnO NPs exhibited a notable photocatalytic efficiency in degrading methylene blue (MB) and methyl orange (MO) under sunshine even in different water samples collected from diverse natural sources, proving them as promising photocatalysts for environmental remediation. The photocatalytic efficiency of the bio-fabricated Kapok-ZnO NPs was impressive, exhibiting a photodegradation rate of up to 99% for MB and 79% for MO under sunlight exposure in different water samples. The novel phyto-fabricated Kapok-ZnO NPs are a beacon of hope for our environment, highlighting incredible photocatalytic efficiency with Pseudo-first-order kinetics and the ability to break down noxious dye pollutants in diverse aquatic environments.